Prognostic value of radiological response to chemotherapy in patients with osteosarcoma. - Shinji Miwa (Public Library of Science (PLoS), 2013)
Background Chemotherapy is essential to improve the prognosis of the patients with osteosarcoma, and the response to chemotherapy is an important prognostic factor. In this study, the impact of various radiological examinations on overall survival (OS) and event-free survival (EFS) was evaluated. Method Eighty-two patients with high-grade osteosarcoma were included in this study, and we evaluated the following factors for prognostic significance: age (≥40 years), gender (male), tumor location (truncal site), metastatic disease, histological response to chemotherapy, radiological response to chemotherapy assessed using X-ray, angiography, CT, MRI, (201)Tl scintigraphy, and (99m)Tc-MIBI scintigraphy ((99m)Tc-MIBI), and combined radiological score (CRS). Results Univariate analyses revealed that metastatic disease, histological response, (99m)Tc-MIBI, and CRS were significantly correlated with OS. Multivariate analyses showed that metastatic disease (OS: HR 35.9, P<0.001; EFS: HR 17.32, P<0.001) was an independent predictor of OS and EFS. Tumor location (HR 36.1, P = 0.003), histological response (HR 31.1, P = 0.036), and (99m)Tc-MIBI (HR 18.4, P = 0.038) were significant prognostic factors for OS. Moreover, CRS was a marginally significant predictor of OS and EFS. Conclusion The chemotherapeutic effects evaluated by (99m)Tc-MIBI and CRS could be considered as prognostic factors in osteosarcoma.